The use of biotechnology in conservation of indigenous animal genetic resources in Mozambique - Maciel, S. (TSAP and ILRI, 2006)
This paper discusses the potential use of biotechnology in the conservation and improvement of indigenous animal genetic resources. National herds, mostly in the hands of the rural communities, are made up mainly of indigenous breeds. Conservation of indigenous livestock must include cryopreservation of semen oocytes and embryos and associated technologies, besides maintenance of living populations. These should be, accompanied by characterisation studies both phenotypic and generic to better understand better existing breeds and prevent the eradication of breeds due to natural or man-made disasters as already happened in Mozambique and is still happening in some parts of the world. Within a clear livestock breeding policy, this would also ensure sustainable utilisation of the indigenous breeds which can result in poverty reduction and food security taking into account community’s intellectual property rights.